Mobile App for IoT-Based Home Security System with Fingerprint Access Control - Wahid, Abdul; Hidayat, Rahmat; Riska, Muhammad (Internet of Things and Artificial Intelligence Journal, 2024)
This study investigates the development and evaluation of an Android-based security system for residential areas, focusing on entrance and exit gate control. Recognizing the limitations of existing systems, we propose an "IoT-based Fingerprint Security Village" application. The system utilizes a prototype development model informed by data collected through interviews, questionnaires, and observations. The application allows residents to monitor and access gates using fingerprint scanners, enhancing security and convenience. To ensure quality, the system underwent rigorous testing based on the ISO 25010 software testing standard. Testing encompassed five key aspects, Functional Suitability: The application achieved a perfect score, indicating it flawlessly performs its intended functions. Portability: The application successfully functioned on all 14 tested Android devices. Performance Efficiency: CPU usage remained exceptionally low (average 0.1%, max 5.5%), and memory usage (average 58.2 MB, max 86.5 MB) demonstrated efficient resource utilization. Security: Testing revealed a low-medium security risk, highlighting areas for potential improvement. Usability: The user-friendliness test yielded a very high score (92%), placing it in the "Very Feasible" category. These results confirm that the "IoT-based Fingerprint Security Village" application effectively meets all evaluated aspects of the chosen software testing standard.